Effect of protein source and quality on feedlot growth performance and rumen fermentation characteristics of Dohne Merino lambs - Erasmus, L.J. (Lourens Jacobus) (University of Pretoria, 2020)
Dissertation (MSc (Agric))--University of Pretoria, 2020.